TECTONIC PALEORECONSTRUCTION OF KOLGAN THICKNESS ON THE BASIS OF TIME SEISMIC CROSS SECTION WITHIN THE DONETSKO-SYRTOVSKY FIELD - S B Denisov; V M Usova (RUDN Journal of Engineering Research, 2016)
Results of the analysis of a paleotectonic structure of the Donetsko-Syrtovsky field are given in article. Ideas of tectonics of the Donetsko-Syrtovsky field were created as a result of generalization of materials of structural, search, prospecting drilling and a complex from seismoprospecting works. As a result are allocated western - Donetsk and east - Syrtovskoye the raisings divided by a superficial deflection. Results of seismoprospecting works 3D have allowed to gain the most detailed impression about a geological structure of the field. As a result of the executed reconstruction of time seismic cross sections and cubes of data no amplitude diagonal and orthogonal tectonic faults which influence on conditions of sedimentation wasn’t established are allocated. The main feature of morphology of all allocated surfaces supposes an inheritance of structural forms at their gradual planation up to surface. It is established that crest parts of local raisings almost flat, and wings abrupt what demonstrates close connection of tectonics of the base and a sedimentary cover. For the paleotectonic analysis, both data of GIS, and time seismic cross section the corresponding borders (reflecting, stratigrafichesky), being alignment surfaces have been chosen. The main sign of surfaces of alignment according to GIS are the lithological differences of breeds sustained on thickness and structure. In a terrigenous section, as a rule, borders of alignment are dated for a closing stage of formation of sedimentic cycles. The mail results of paleotectonic analysis of time seismic cross section: deposits of kolgan thickness were formed in the conditions of an active phase of the tectonic process dividing the Donetsk and Syrtovsky raisings; the active syndepositional phase of tectogenesis has exerted impact on nature of distribution of sandy material in deposits of kolgan thickness.